2014
DOI: 10.1142/s1793292014500878
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Analysis for Fracture Behavior of Graphene Sheets With v-Shaped Notches Under Tension

Abstract: Molecular dynamics (MD) simulations are performed to study the fracture behavior of armchair and zigzag graphene sheets with V-shaped notches subjected to tensile loading. The e®ects of temperature and notches depth on the fracture characteristics of the graphene sheets are examined. The results show that the cracks propagate from the notch tip along the direction perpendicular to the loading axis for armchair sheets. This is di®erent from the zigzag graphene propagating along the direction of 45 from the load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…While in pre-strained graphene sheets, crack propagation speed is independent of the length, location and number of inserted crack. For the graphene sheet with a hole in its center, Fang et al [51,52] found that the fracture strength, strain and Young's modulus decrease while the Poisson's ratio increases with the hole size increasing. For the graphene sheet with v-shape crack, they also found that the crack propagates from the crack tip along the direction perpendicular to the loading axis for armchair sheet and along the direction of 45° from the loading axis for zigzag sheet.…”
Section: Introductionmentioning
confidence: 99%
“…While in pre-strained graphene sheets, crack propagation speed is independent of the length, location and number of inserted crack. For the graphene sheet with a hole in its center, Fang et al [51,52] found that the fracture strength, strain and Young's modulus decrease while the Poisson's ratio increases with the hole size increasing. For the graphene sheet with v-shape crack, they also found that the crack propagates from the crack tip along the direction perpendicular to the loading axis for armchair sheet and along the direction of 45° from the loading axis for zigzag sheet.…”
Section: Introductionmentioning
confidence: 99%